Association of BMI on Systolic and Diastolic Blood Pressure In Normal and Obese Children (Nepal Journal of Epidemiology, 2011)
Background Definition of childhood overweight/obesity should aim to identify children with excess body fat in order to treat the associated adverse health outcomes. Objective To investigate relationship between Body Mass Index (BMI) and systolic blood pressure (SBP) and diastolic blood pressure (DBP) values in children between the ages of 6 and 14 year old. Materials and Methods Secondary data gathered from public health screening days at Child Health and Diseases Polyclinic of Kocaeli Metropolitan Municipality Maternity and Children Hospital on 1899 children. Each child was classified on the basis of age- and sex-specific Body Mass Index percentile (BMI%) as normal weight (BMI% < 85th), overweight (BMI% ≥ 85th and < 95th), or obese (BMI% ≥ 95th). Systolic and diastolic blood pressures were compared among age-sex-BMI percentile groups. Results SBP and DBP values are higher in obese and overweight children compared to normal children. Among all children in this study, being overweight and obese increased the likelihood of elevated SBP and DBP values after adjusting for age.  Blood pressure (BP) is increasing with increasing BMI in all age groups (6 to 14 year old) and this is also found at a young age. The same trend is also present within the normal BMI% group. Conclusions Our results show that BMI is associated with elevated systolic and diastolic blood pressure in overweight and obese children as well as children in normal BMI% group. BP is increasing with increasing BMI values even in normal group but the increase is more in obese children. Hence, maintaining age related normal growth increase in the BMI in childhood is important in preventing higher BP values later in life.Keywords: Body Mass Index; BMI; Blood pressure; Children DOI: http://dx.doi.org/10.3126/nje.v1i3.5574 Nepal Journal of Epidemiology 2011;1(3) 101-105